Antimicrobial mechanism of luteolin against Staphylococcus aureus and Listeria monocytogenes and its antibiofilm properties. (May 2020) - Qian, Weidong; Liu, Miao; Fu, Yuting; Zhang, Jianing; Liu, Wanting; Li, Jingyuan; Li, Xiang; Li, Yongdong; Wang, Ting
Abstract: Luteolin (LUT) is a naturally occurring compound found in a various of plants. Few recent studies have reported LUT antimicrobial activities against bacterial pathogens, however, the fundamental LUT mediated antimicrobial mechanism has never been elucidated. This study aimed to investigate the antimicrobial activities of LUT and its mode of action against Staphylococcus aureus and Listeria monocytogenes, either as planktonic cells or as biofilms. Here, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) of LUT against S. aureus and L. monocytogenes were determined using the broth microdilution method, and the antimicrobial mode of LUT was elucidated by evaluating the variations in both cell membrane integrity and cell morphology. Moreover, the biofilm inhibition was measured by crystal violet staining assay, while its qualitative imaging was achieved by confocal laser scanning microscope and field emission scanning electron microscope. MIC and MBC values of LUT against S. aureus were 16–32 and 32–64 μg/mL, and 32–64 and 64–128 μg/mL for L. monocytogenes . LUT destroyed the cell membrane integrity, as evidenced by a significant increase in the number of non-viable cells, and well-defined variations in cell morphology. Moreover, LUT presented robust inhibitory effects on the biofilm formation, enhanced antibiotics diffusion within biofilms and killed efficiently mono- and dual-species biofilm cells. Overall, LUT demonstrates potent antimicrobial properties on planktonic and biofilm cells, and the biofilm formation, and thus has the potential use as a natural food preservative in foods. Highlights: The antimicrobial and antibiofilm activity of luteolin against S. aureus and L. monocytogenes was investigated. Luteolin presents impairment effect on S. aureus and L. monocytogenes cell membrane. Luteolin restrains biofilm formation of S. aureus and L. monocytogenes. Luteolin can kill biofilm cells of S. aureus and L. monocytogenes.